多馈线辐射式配电网接入多个分布式电源的故障区段诊断方法 (2018)
本发明公开了种多馈线辐射式配电网接入多个分布式电源的故障区段诊断方法，应用于配电网在接入分布式电源后的故障区段判断。包括数据采集模块、逻辑判断模块和远动执行模块。数据采集模块用于采集电流元件和方向元件的信息，远动执行模块控制馈线断路器开断，逻辑判断模块包括初始定位模块、分布式电源区段判断模块和分布式电源后段判断模块。本方法结合原保护接线实际情况，不需要在原有配电网的每个保护装置上加入方向元件，也不需要重新整定保护装置上的定值，而是直接通过判断配电网中馈线出口处电流变化量、分布式电源所接方向元件、每个保护电流比较环节输出，经过所述功能模块实现故障区段的定位，具有良好的经济性和可行性。 The invention discloses a fault section diagnosis method for a multi-feeder radial distribution network connected with multiple distributed power supplies, and is used for fault section judgment after a distribution network is connected with distributed power supplies. Included are a data acquisition module, a logic judgment module and a telecontrol execution module. The data acquisition module is used for acquiring information of a current element and a direction element, the telecontrol execution module controls the on and off of a feeder circuit breaker, and the logic judgment module comprises an initial positioning module, a distributed power supply section judgment module and a distributed power supply rear section